2004
DOI: 10.1007/s10006-004-0529-9
|View full text |Cite
|
Sign up to set email alerts
|

Stabilit�t der Osteosynthese bei Gelenkwalzenfrakturen in Klinik und biomechanischer Simulation

Abstract: The newly developed osteosynthesis system using a retroauricular approach based on 1.7 mm small fragment screws makes maxillomandibular immobilization unnecessary. The extra-articular position of the screw heads prevents scar-induced articular limitations. Preexisting degenerative alterations of the TMJ soft tissues, however, will affect functional results adversely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…The use of biodegradable screws has a number of limiting factors: poor mechanical stability, difficult handling properties, and time-consuming fixation. The tapping of threads takes a long time and limits easy handling, particularly for small diameter screws, and the insertion is limited by the relation of the axis of the screw to the osteosynthesis plate (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The use of biodegradable screws has a number of limiting factors: poor mechanical stability, difficult handling properties, and time-consuming fixation. The tapping of threads takes a long time and limits easy handling, particularly for small diameter screws, and the insertion is limited by the relation of the axis of the screw to the osteosynthesis plate (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al, [4] who also used two lateral screws for the internal fixation of the intracapsular fracture, reported that two lateral screws for bicortical osteosynthesis resist the lateral dislodging forces and prevent the proximal rotation of the fragments. Based on the biomechanical simulations they performed Neff et al [19] reported that osteosynthesis with one lag screw is insufficient in providing the rotational stability. Nevertheless, the satisfactory results of Yang et al [1] and Luo et al [3] have been achieved by the use of a single bicortical screw.…”
Section: Discussionmentioning
confidence: 99%
“…Different authors have reported on the application of microand miniplates, lag screws, cannulated screws, small-fragment positional screws, bioresorbable pins and screws, each with varying rates of success. [10][11][12][13][14][15] According to the literature, the standard technique for internal xation of condylar head fragments is titanium screw osteosynthesis via the lateral end of the ascending ramus. 14,16 Due to the complex loading conditions of the TMJ in normal mastication, at least two xation screws are necessary to compensate for rotational and share stresses.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] According to the literature, the standard technique for internal xation of condylar head fragments is titanium screw osteosynthesis via the lateral end of the ascending ramus. 14,16 Due to the complex loading conditions of the TMJ in normal mastication, at least two xation screws are necessary to compensate for rotational and share stresses. 10,12,13 The application of two-screw xation for dia capitular condylar head fractures was rst described by Rasse et al and later modi ed by Neff et al, who improved the technique and proved its e cacy in clinical and biomechanical studies.…”
Section: Introductionmentioning
confidence: 99%